(untitled) (Research, Society and Development, 2020)
The objective of this aticles was to analyze the presence of the Brazilian Sign Language (Libras) discipline in dentistry courses in northeastern Brazil. This study was cross-sectional and descriptive, with data collection available on the website of the Ministry of Education (MEC) and the Federal Council of Dentistry (CFO). All universities in northeastern Brazil that offer the dentistry course and were registered in the MEC or CFO were included, and institutions that did not present the curricular components on their respective sites were excluded. The research universe was 147 universities, however after the inclusion and exclusion criteria, a sample of 114 colleges was obtained. The information was recorded in the Statistical Package for Social Sciences (SPSS) for Windows, version 20.0, and worked by descriptive statistics. Of the 114 institutions consulted, 71 (62.28%) presented the discipline of Libras, being 60 (84.51%) in private university and the other 11 (15.49%) in public universities, in addition, 66 (92.95%) are of the optional type and only 5 (7.05%) are of the mandatory type, with half-yearly workloads ranging from 20hrs to 80hrs in some states. Thus, it can be concluded that a significant portion of higher education institutions in the northeast region do not have Libras in the curriculum of the dentistry course, which can lead to difficulty in communicating with deaf patients.